Validation of a new mass screening tool for cognitive impairment: Cognitive Assessment for Dementia, iPad version - Onoda K; Hamano T; Nabika Y; Aoyama A; Takayoshi H; Nakagawa T; Ishihara M; Mitaki S; Yamaguchi T; Oguro H; Shiwaku K; Yamaguchi S (Clinical Interventions in Aging, 2013)
Keiichi Onoda,1 Tsuyoshi Hamano,2 Yoko Nabika,1 Atsuo Aoyama,1 Hiroyuki Takayoshi,1 Tomonori Nakagawa,1 Masaki Ishihara,1 Shingo Mitaki,1 Takuya Yamaguchi,1 Hiroaki Oguro,1 Kuninori Shiwaku,3 Shuhei Yamaguchi1 1Department of Neurology, 2Center for Community-Based Health Research and Education, Shimane University, Izumo, 3Shimane University, Matsue, Shimane, Japan Background: We have developed a new screening test for dementia that runs on an iPad and can be used for mass screening, known as the Cognitive Assessment for Dementia, iPad version (CADi). The CADi consists of items involving immediate recognition memory for three words, semantic memory, categorization of six objects, subtraction, backward repetition of digits, cube rotation, pyramid rotation, trail making A, trail making B, and delayed recognition memory for three words. The present study examined the reliability and validity of the CADi. Methods: CADi evaluations were conducted for patients with dementia, healthy subjects selected from a brain checkup system, and community-dwelling elderly people participating in health checkups. Results: CADi scores were lower for dementia patients than for healthy elderly individuals and correlated significantly with Mini-Mental State Examination scores. Cronbach’s alpha values for the CADi were acceptable (over 0.7), and test–retest reliability was confirmed via a significant correlation between scores separated by a one-year interval. Conclusion: These results suggest that the CADi is a useful tool for mass screening of dementia in Japanese populations. Keywords: dementia, mass screening, early detection, iPad